May Growth Lead to Higher Deprivation Despite Higher Satisfaction? - Wodon, Quentin; Yitzhaki, Shlomo (2012)
In a relative deprivation framework, unless inequality is reduced, growth is associated with both higher satisfaction and higher deprivation. This may help explain the discontent with growth despite its benefits. As is well known in the literature, knowledge of the population's mean income and Lorenz curve is all that is needed to analyze a distribution, so that this can also be used to assess the satisfaction and deprivation of each individual. Given the normalization used to derive the satisfaction and deprivation measures, satisfaction and deprivation add up to the mean income for the population as a whole as well as for each individual.